2015
DOI: 10.1016/j.cell.2015.07.009
|View full text |Cite
|
Sign up to set email alerts
|

RAG Represents a Widespread Threat to the Lymphocyte Genome

Abstract: SUMMARY The RAG1 endonuclease, together with its cofactor RAG2, is essential for V(D)J recombination but is a potent threat to genome stability. The sources of RAG1 mis-targeting and the mechanisms that have evolved to suppress it are poorly understood. Here, we report that RAG1 associates with chromatin at thousands of active promoters and enhancers in the genome of developing lymphocytes. The mouse and human genomes appear to have responded by reducing the abundance of “cryptic” recombination signals near RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
148
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(166 citation statements)
references
References 48 publications
17
148
0
1
Order By: Relevance
“…5C). This finding is consistent with our recent RAG1 ChIP-seq data that revealed the binding of RAG1 at a wide range of intensi-ties to thousands of active promoters in developing B and T cells (38). We conclude that RAG1 binding is not limited to regions containing RSSs, in contrast to the conclusions of our previous study (25), and that the association of RAG1 with chromatin might be mediated by various types of interactions, including sequence-specific and nonspecific DNA binding and interactions with nucleosomes.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…5C). This finding is consistent with our recent RAG1 ChIP-seq data that revealed the binding of RAG1 at a wide range of intensi-ties to thousands of active promoters in developing B and T cells (38). We conclude that RAG1 binding is not limited to regions containing RSSs, in contrast to the conclusions of our previous study (25), and that the association of RAG1 with chromatin might be mediated by various types of interactions, including sequence-specific and nonspecific DNA binding and interactions with nucleosomes.…”
Section: Discussionsupporting
confidence: 82%
“…This might be relevant for analyses of initial binding using an inducible expression system (as in this study), given that individually expressed RAG1 core and RAG2 core proteins interact with only a modest affinity, with a K D (equilibrium dissociation constant) value of ϳ0.4 M (45). We also note that our recent ChIP-seq analysis using mouse thymocytes revealed that RAG1 binding was reduced in intensity and less well focused at regions of high H3K4me3 levels in the absence of RAG2 than in its presence (38). These results (which represent a steady-state analysis) are more in keeping with the models derived from in vitro kinetic studies (44).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations